Asking 'What about' questions in chronic illness self-management meetings. Issue 6 (June 2016) - Fasulo, Alessandra; Zinken, Jörg; Zinken, Katarzyna
Highlights: Patients in the Start Insulin meetings asked numerous 'What about' questions. The single-unit version of the question was prevalent, unlike previous findings. The question embedded new requests for information in current or prior activities. The use of 'What about X' reflected adjustments to constraints on information seeking. Abstract: Objectives: This study investigates 'What about' questions asked by patients in the course of diabetes self-management groups led by nurses, and explores their functions in these empowerment-informed settings. Methods: Conversation Analysis of 24 video-recorded sessions of a Start Insulin Group Programme for patients with type 2 diabetes, in a diabetes centre in the South of England. The groups included 2–7 patients and were led by 5 nurses, all of whom had received training in the empowerment approach. Results: The analysis revealed a prevalence of single-unit 'Whatabout X' questions and found that they were used to embed requests for information in current or just closed activities. The nurses always provided the information, but could ask patients to specify the content of the question and collaborate to the answer. Conclusion: The analysis suggests that the short form of the question may be adapting to the nurses' restraint in giving recommendations or immediate responses to information seeking-questions. Practice implications: When healthcare communication practices are shaped in observance to a theoretical approach, such as empowerment, it is recommendable that practitioners monitor not only what they do, but also how patients change their habitual forms of speech in response.